Sub-10 nm patterning with DNA nanostructures: a short perspective. (10th October 2017) - Du, Ke; Park, Myeongkee; Ding, Junjun; Hu, Huan; Zhang, Zheng
Abstract: DNA is the hereditary material that contains our unique genetic code. Since the first demonstration of two-dimensional (2D) nanopatterns by using designed DNA origami ∼10 years ago, DNA has evolved into a novel technique for 2D and 3D nanopatterning. It is now being used as a template for the creation of sub-10 nm structures via either 'top-down' or 'bottom-up' approaches for various applications spanning from nanoelectronics, plasmonic sensing, and nanophotonics. This perspective starts with an histroric overview and discusses the current state-of-the-art in DNA nanolithography. Emphasis is put on the challenges and prospects of DNA nanolithography as the next generation nanomanufacturing technique.